PELAKSANAAN KONSEP KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH DALAM MENINGKATKAN MUTU MADRASAH DI MAN 1 GARUT - Eep Saepuloh; Ummu Salamah; Nenden Munawaroh (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This research analyzes the transformation of MAN 1 Garut into a leading madrasah through transformational leadership amidst intense educational competition. It aims to analyze the construction of concepts, implementation, and determinants, while reconstructing an effective leadership model to enhance institutional quality. Utilizing a descriptive qualitative method, data were collected through in-depth interviews with nine key informants, observation, and documentation, validated via triangulation.The results indicate that leadership is operationalized through a "Marathon Runner" philosophy, where the leader acts as a "Pacer" to maintain innovation consistency through a "Super Team" mechanism and "Silent Leadership" strategies. The power of "Spiritual Legitimacy" is proven to create emotional loyalty and a strong "Inner Contract" between the leader and staff. This transformation is empirically evidenced by international achievements at IMEC 2025 and the "MONTIME" work culture shift. Although hindered by bureaucratic rigidity, social capital in the form of public trust serves as the primary support. The novelty of this research is the formulation of the "Theocentric-Transformational Leadership Model Based on Exemplarity" (Imamiyah Leadership). This model synergizes modern management with spirituality to create sustainable quality, transcending conventional transformational models that tend to be secular.